Interspecific variation of heavy metal concentrations in the different tissues of tropical intertidal gastropods from Malaysia. - Edward Thomas, Franklin Berandah; Yap, Chee Kong; Tan, Soon Guan (Taylor & Francis, 2010)
The present study aims to determine the concentrations of Cd, Cu, Fe, Ni, Pb, and Zn in the different tissues of five species of tropical intertidal gastropods from Malaysia. Each of the species have organs/tissues that highly accumulated certain metals. For Cu, the mantles of Cerithidea obtusa, Pugilina cochlidium, and Murex trapa; and the digestive caeca of Thais sp. and Chicoreus capucinus highly accumulated Cu. The shells of Chi. capucinus and M. trapa, the digestive caeca of P. cochlidium, and the digestive glands of Thais sp. and Chi. capucinus highly accumulated Cd. The tentacles and the digestive caeca of Cer. obtusa and P. cochlidium, respectively, highly accumulated Zn, the digestive glands of Thais sp., Chi. capucinus, and M. trapa also highly accumulated Zn. The shells of most of the gastropods accumulated high levels of Pb and Ni. The opercula of most of the gastropods, besides the digestive glands for Thais sp., accumulated high levels of Fe. The present study on interspecific variations of heavy metals in gastropods provided information on differences of metal distributions in the different tissues, which could be useful in proposing potential tissues as better biomonitoring tools of heavy metal bioavailabilities in the coastal waters of Peninsular Malaysia.